Developing Characters Based on Local Wisdom of Bali in Teaching Physics in Senior High School (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
Human resources with good characters are badly needed in a national development. Hence, developing characters, especially the development of characters based on local wisdom is highly needed. This study was part of a study of local culture-based Physics model of teaching at senior high school, i.e., the need analysis and conceptual model prototype stage. The subjects were 20 physics teachers who had at least 10 years of teaching physics experience at public and private senior high schools in Singaraja, Bali. The study used questionnaire, observation guide, and interview as the instruments for collecting the data. The data were analyzed by a descriptivequalitative analysis. The result showed that (1) Nine Balinese local wisdom-based characters could be developed in physics teaching; (2) The method that is appropriate for the local wisdom-based development of characters is inquiry from various perspectives, discussion, and demonstration; (3) The core procedure of teaching that can develop the students’ character are exploration, focusing attention, inquiry from various perspectives (scientific, sociocultural, historical), elaboration, and confirmation.